In House Training: Penyusunan Perencanaan Pembelajaran pada Modul Ajar dalam Implementasi Kurikulum Merdeka - Yulistia, Annisa; Wicaksono, Lungit; Khairani, Fadhilah; Izzatika, Amrina (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2024)
The existence of the Merdeka Curriculum policy poses various challenges and obstacles for educators. With these various challenges and obstacles, educators, and school principals want training and assistance in preparing teaching modules in accordance with the independent curriculum policy through in-house training (IHT) activities. The purpose of carrying out this activity is so that the training participants have insight, understanding and can compile and apply teaching modules at the elementary school (SD) level. The methods used to achieve these goals are lectures, discussions, problem solving, and practice. The form of evaluation carried out in this service activity is divided into 4 stages, namely initial, process, final, and impact evaluation. The results of this activity are 1) in the initial evaluation, teachers have never made teaching modules, but in preparing lesson plans they are quite skilled; 2) in the IHT process, teachers began to understand the planning and learning process expected in the implementation of the independent curriculum; 3) the end of the IHT activity shows that teachers begin to understand the preparation of CP-TP-ATP as outlined in the teaching module; 4) this activity has an impact on reactivating the learning community in schools to share best practices in preparing lesson plans.